Praktik Self-reward di Kalangan Mahasiswi FISIP Unsoed - Syahla Zein Azizah; Niken Paramarti Dasuki; Soetji Lestari (Universitas Lambung Mangkurat, 2026)
Self-reward has become a widespread phenomenon among students, including female students of FISIP Unsoed. Self-reward is a way of self-love by giving rewards, appreciation, giving gifts, and appreciating efforts and achievements that have been passed. This study aims to describe the meaning and practice of self-reward among female students of FISIP Unsoed. This study uses a descriptive qualitative method. Data collection methods include observation, interviews, and documentation. A purposive sampling technique was used to determine informants with a total of 7 female students of FISIP Unsoed. The results of this study indicate that the meaning of self-reward among female students is as a form of appreciation for oneself for past achievements. Then, the practice of self-reward among female students is more often to buy food. In addition, the practice of self-reward is also carried out online, especially on Instagram. Instagram is a medium for self- actualization and self-expression when female students do self- reward. Female students have good control and boundaries in practicing self-reward.